1973
DOI: 10.1063/1.1680340
|View full text |Cite
|
Sign up to set email alerts
|

Vibration-vibration equilibration in laser excited CH3F and CH3F-X mixtures

Abstract: The infrared fluorescence risetime of the ν1,ν4 C–H stretching modes of CH3F has been measured in CH3F-rare-gas mixtures after pumping of the ν3 C–F stretching modes with a Q-switched CO2 laser. The pressure-dependent rate of rise was found to be 122 ± 25 msec−1 · torr−1 in pure CH3F. The effect of rare gases on this rate process was also studied and found to be consistent with a vibration-vibration filling mechanism for ν1,ν4 involving a small amount of energy transfer (≤ 75 cm−1) into the translational/rotat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1973
1973
2014
2014

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…1) gives (27) where fji = v~/vf. Therefore the general temperature equation is equivalent to the fundamental coupling equation (21) except that the energy of mode II J has been replaced by an "adjusted" energy f}IEr Equation (27) illustrates that the details of the vibrational energy transfer pathway will affect the steady state temperature· distribution. As in the previous case of fundamental coupling, the temperature of the various modes will differ at vibrational steady state in a manner determined by the mode energy gaps.…”
Section: A Linear Coupling Between Modes Through the Lowest (V= 1) Smentioning
confidence: 99%
“…1) gives (27) where fji = v~/vf. Therefore the general temperature equation is equivalent to the fundamental coupling equation (21) except that the energy of mode II J has been replaced by an "adjusted" energy f}IEr Equation (27) illustrates that the details of the vibrational energy transfer pathway will affect the steady state temperature· distribution. As in the previous case of fundamental coupling, the temperature of the various modes will differ at vibrational steady state in a manner determined by the mode energy gaps.…”
Section: A Linear Coupling Between Modes Through the Lowest (V= 1) Smentioning
confidence: 99%
“…Such collisions are also the ones conSidered in the already-mentioned earlier works. [1][2][3][4][5] However, in those works the molecular rotations were assumed to be frozen and the recoil velocity was calculated from the energy conservation alone. Here, the recoil velocity will be determined from the energy and angular momentum conservation laws.…”
Section: The Modelmentioning
confidence: 99%
“…All these make CH 3 F a good probe to study nuclear spin statistics and spin conversion in helium nanodroplets. 26,27 The CH 3 F-He interaction has been studied extensively in the past several decades, focusing on vibrational relaxation, [28][29][30][31] scattering, [32][33][34] and helium pressure broadening, [35][36][37][38] empirical potentials have been reported. 32,39 In 2003, Bussery-Honvault et al 41 performed symmetryadapted perturbation-theory (SAPT) 40 calculations of the CH 3 F-He PES and used it to calculate pressure broadening coefficients, obtaining good agreement with the experimental results of Willey et al 36 In 2005, a microwave spectrum for the ortho-CH 3 F-He dimer was first observed by Higgins and Klemperer, 42 who assigned several rotational transitions based on theoretical bound state calculation using a 3D CH 3 F-He PES computed at the MP4 level.…”
Section: Introductionmentioning
confidence: 99%